What do resource-oriented approaches mean to general practitioners and how can they be facilitated in primary care?: a qualitative study - Prüfer, Franziska; Joos, Stefanie; Miksch, Antje (Evidence-based complementary and alternative medicine, 2013)
Although resource orientation, as a part of health promotion, should play a major role in general practice, the anchoring and realization of resource-oriented approaches remain small in Germany. The aim of this study was to analyze what resource orientation means to general practitioners (GPs) and develop strategies as to how this can be facilitated in GP practice. Within a qualitative research approach, 19 semi-structured telephone interviews were recorded, transcribed, and analyzed using qualitative content analysis. Within the interviews, the inclusion of the patients’ individual resources is described as core competence of GPs. Supporting the patients’ disease coping strategies and self-help were seen as important by GPs. However, perceptions as to which resources are considered to be fundamental ranged widely across the participant group. The results confirm the important role of resource-oriented approaches in general practice. However, a general definition of resource orientation is needed. In addition, working conditions for GPs need to be taken into account to ensure that these contribute to a healthy work-life balance. The need for GP training was identified to improve communication skills. Further integration of GPs in health promotion and communal structures would be beneficial.